Assesment of Root Apices Closureof Permanent Incisors and First Molars in Digital Orthopantomographs: A Pilot Study From Pakistan - Wahaj Anees, Falak Murad Shah, Jamal Nasir Khan, Naima Jabeen, Hafiz Muhammad Abu Bakar Siddique, Suman Shoro, Sadia Akram, Irfan Ullah (Pakistan Journal of Medical & Health Sciences, 2022)
Objective:The purpose of the current study is to assess the degree of closure of the root apices of primary molars and permanent incisors in young children. Study Design:Retrospective study Place and Duration: This study was carried out at Department of Oral Biology, Sardar Begum Dental College, Peshawar from January, 2022 to July 2022. Methods: There were 130 patients of both genders with ages 4-16 years were presented. After obtaining informed written consent, the enrolled cases’ detailed demographics, including age, sex, body mass, and locale, were computed. Digital orthopantomographs of all the patients were taken. Chi square test was used to assess differences among closure of root apices of permanent incisors and first molars among all cases. SPSS 22.0 was used to analyze all data. Results:Among 130 included cases, 80 (61.5%) were females and the rest were males 50 (38.5%).Mean age of the cases were 12.6±4.72 years. 85 (65.4%) cases had body mass index <18 kg/m2 and 45 (34.6%) patients had BMI >18kg/m2. There were 76 (58.5%) cases had urban and 54 (41.5%) patients had rural residency. Permanent incisors were 82 (63.1%) and first molars were 48 (36.9%). At age between 5-9 years frequency of closed root apices of mandibular central incisors was 50 (60.9%) and closed maxillary first molars were 22 (51.2%). At age 10-15 years number of closed root apices of central incisors were 65 (79.3%) and closed root apices of first molars were 30 (62.5%) with p value <0.003. Conclusion:In this study, we came to the conclusion that the majority of root apices of permanent incisors and first molars in children in the studied sample close early compared to earlier reports, which is consistent with the pattern of emergence of permanent teeth previously reported in children. Keywords:Root Apices, First Molars, Permanent Incisors, Children